2014
DOI: 10.1111/apa.12676
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system processing of emotions in children with nocturnal enuresis and attention‐deficit/hyperactivity disorder

Abstract: Children with NE processed emotions differently from children with ADHD and controls. Children with NE + ADHD processed emotions the most intense, displaying interaction effects of the central nervous system that cannot be explained by each disorder alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Children with functional gastrointestinal disorders are more susceptible to developing emotional and behavioral symptoms, and electrophysiological studies have shown that children with fecal incontinence have increased responses in the processing of emotions; this suggests neurobiological vulnerability and could possibly be due to “cross‐talk” between the ENS and CNS. The responses are even more pronounced than in children with enuresis …”
Section: Other Factorsmentioning
confidence: 88%
See 1 more Smart Citation
“…Children with functional gastrointestinal disorders are more susceptible to developing emotional and behavioral symptoms, and electrophysiological studies have shown that children with fecal incontinence have increased responses in the processing of emotions; this suggests neurobiological vulnerability and could possibly be due to “cross‐talk” between the ENS and CNS. The responses are even more pronounced than in children with enuresis …”
Section: Other Factorsmentioning
confidence: 88%
“…The responses are even more pronounced than in children with enuresis. 76 The role for the gut microbiome in sensitization is speculative as it has been postulated that bidirectional communication between the microbiome and brain plays a role in depression and bowel symptoms. 77 Bacteriuria is associated with a range of LUT symptoms, and the role of a putative bladder microbiome in the sensitization of spinal neurons needs to be further explored.…”
Section: Other Factorsmentioning
confidence: 99%
“…For example, one study found that parental sensitivity in early childhood is positively associated with markers of more optimal brain development at age 8, and suggested that stimulation provided by sensitive caregivers can facilitate increases in brain volume and cortical thickness 39 . Thus, parenting may contribute to the maturational deficits of the central nervous system that have been postulated to underlie the development of enuresis 5,40 . This also raises the intriguing possibility that interventions that promote authoritative parenting may reduce children’s risk of developing enuresis and possibly even the psychopathology that is subsequently associated with enuresis.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results also indicate that functional impairment is evident in these youth even before they are eligible for a diagnosis of enuresis, and that later observations of impairment reflect earlier difficulty in functioning. Indeed, evidence suggests that enuretic children are likely to have executive functioning problems 40 , which could impact their daily living. In contrast, after accounting for preexisting impairment, primary enuresis does not appear to have an additional long-term impact on functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Children with MNE showed more intense responses than controls, whereas those with ADHD did not differ from the controls. Children with MNE + ADHD elicited the strongest responses [109]. They concluded that children with MNE process emotions differently from children with ADHD and controls.…”
Section: Psychological Disordersmentioning
confidence: 96%